2016
DOI: 10.1017/jfm.2016.665
|View full text |Cite
|
Sign up to set email alerts
|

Skin-friction generation by attached eddies in turbulent channel flow

Abstract: Despite a growing body of recent evidence on the hierarchical organization of the selfsimilar energy-containing motions in the form of Townsend’s attached eddies in wallbounded turbulent flows, their role in turbulent skin-friction generation is currently known very little. In this paper, the contribution of each of these self-similar energycontaining motions to turbulent skin friction is explored up to Reτ ≃ 4000. Three different approaches are employed to quantify the skin-friction generation by the motions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 83 publications
(154 reference statements)
5
59
0
Order By: Relevance
“…friction generation). Smart enforcing of this transfer at large scale was demonstrated to reduce a substantial amount of drag by modifying the self-sustaining processes at other scales [36], and its artificial inhibition also yielded a significant amount of drag reduction at high Reynolds numbers [54,69,72], suggesting the practical importance of the self-sustaining processes in skin-friction control.…”
Section: Relation To Townsend's Attached Eddiesmentioning
confidence: 95%
See 1 more Smart Citation
“…friction generation). Smart enforcing of this transfer at large scale was demonstrated to reduce a substantial amount of drag by modifying the self-sustaining processes at other scales [36], and its artificial inhibition also yielded a significant amount of drag reduction at high Reynolds numbers [54,69,72], suggesting the practical importance of the self-sustaining processes in skin-friction control.…”
Section: Relation To Townsend's Attached Eddiesmentioning
confidence: 95%
“…For instance, it has been recently experimentally shown [71] that proper orthogonal decomposition (POD) modes extracted in the logarithmic region from Princeton's superpipe data are self-similar with respect to the spanwise length scale and/or the distance from the wall. Furthermore, it has recently been found that most turbulent skin friction at sufficiently high Reynolds numbers (Re τ > 1000) is generated by the self-similar self-sustaining motions in the logarithmic region [69,72]. In particular, the coherent lift-up effect was found to play a crucial role in transferring the streamwise momentum to the near-wall region (i.e.…”
Section: Relation To Townsend's Attached Eddiesmentioning
confidence: 99%
“…τ x,rms /τ x = 0.298 + 0.018 ln(Re τ ), where Re τ = u τ δ/ν, u τ is the friction velocity, ν is the kinematic viscosity and δ is the boundary-layer thickness (or channel half-height). The Reynolds number dependence of τ x,rms suggests that large-scale energy-containing motions populating the logarithmic and outer regions in high-Reynolds-number wall turbulence have non-negligible influences on the near-wall dynamics and, hence, on the wall friction (Abe et al 2004;Örlü & Schlatter 2011;de Giovanetti, Hwang & Choi 2016;Renard & Deck 2016;Baidya et al 2019;Fan et al 2019a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the question of what the main energy-containing eddies really are is very important, as these eddies would play the central role in momentum and mass transfer due to their energy-containing nature -indeed, it was recently shown that the energy-containing eddies which scale with the distance from the wall are the dominant source of turbulent skin-friction generation at high Reynolds numbers (de Giovanetti et al 2016). Recently, some important statistical and dynamical features of these main energy-containing eddies have also been reported.…”
Section: Introductionmentioning
confidence: 99%